Post Trips Patenting Regime and Pharmaceutical Industry of India with Reference to North West Region: Changing Paradigms, Perspectives and Pragmatics - Mishra, Sunita (My University, 2010)
The Indian pharmaceutical industry initially, governed by the Patents Act of 1911, allowed the MNCs to take advantage and they patented heavily in the country and the indigenous firms were legally prevented from manufacturing most of the new drugs introduced by the transnational corporations (TNCs) during the life of the patent. The Patent Act of 1911, amended in 1970 provided protection for the processes of manufacturing the drug for seven years from the date of filing the application or for five years from the date of the grant of the patent. It was harshly criticized by the multinational companies operating in India at that time on the grounds that it would reduce the incentives for investments in that sector. A large number of indigenous and smaller enterprises entered the market and competed with existing firms. Over the years, it became a much more fragmented industry. The period 1970-95, generally known as the pre-TRIPS period, has been considered as a flourishing phase of the Indian pharmaceutical industry. The scenario changed after world trade organization (WTO), 1995 and India, being a signatory member of WTO, adopted TRIPS. Under TRIPS, all countries have to provide for protection of product patents from January 1, 1995. Developing countries like India, which did not have a regime of product patents, could take advantage of a transition period of ten years until January 1, 2005. However, perceptions about IPRs in India also changed over time and a paradigm shift occurred in the industry and caused a marked shift in India’s policy around 1998-99. Industry bodies and various groups changed their stand and now took a pro-patent view. Accordingly ‘The Patent Act 1970’ was amended and under the Patents (Amendment) Act, 2005 patents are to be granted both for products and processes for all the inventions in all fields of technology. As a result, reverse engineering possibilities, hitherto available to the pharmaceutical industry, will only be limited to those drugs that will go off-patent. The period 1995-2008 (i.e., the post-TRIPS period) is thus very important for the pharmaceutical industry of India. In the above backdrop, the present study examines the impact of TRIPS on the pharmaceutical industry of India in the the post-TRIPS period in terms of patents, R&D and exports. The analyses have been done at the industry level, at the level of selected leading pharmaceutical companies and also for the sample survey of 100 firms selected from the north west region of India. The results of the industry level data depict that patents have increased in the pharmaceutical industry of India in the post-TRIPS period. Growth of R&D of the industry as a whole has been higher in the post-TRIPS period as compared to the pre-TRIPS period. Growth of exports is also higher in the post-TRIPS period as compared to the pre-TRIPS period. The results of the present study also show that patenting activities of the leading pharmaceutical companies have improved consistently. Not only the patent filing has increased, the patents granted have also increased in the post-TRIPS period. In the case of ANDA filings with USFDA and DMF filings, the situation has dramatically changed in the last few years. Now, besides Ranbaxy and DRL, other firms like Cipla and Sun Pharmaceuticals, Cadilla, Aurobindo and Glenmark are also increasing ANDA and DMF filings. The firm level analyses of the north west region depict that the firms have reported a shift to better technology, an increase in in-house R&D, enhancement in the proportion of turnover spent on R&D, enlargement of the number of products introduced and augmented sales. The analyses also reflect that the firms in the north west region of India are preparing themselves for the change, they do not perceive Schedule M as a hasty decision and are not threatened by MRP based excise duty on the existing prices although the existing literature does not support it (Cygnus, 2006; Dey, 2007; Jaisankar, 2007; Jaikumar, 2008). These results have further been tested by the regression analysis. Overall results depict an improvement in patenting, R&D and exports in the post-TRIPS period.
Ph.D
Keywords: TRIPS, PHARMACEUTICAL INDUSTRY; PARADIGMS, PERSPECTIVES AND PRAGMATICS